Fabrication of gold nanoparticles in confined spaces using solid-phase reduction: Significant enhancement of dispersion degree and catalytic activity. (2nd February 2017) - Xing, Zhi-Min; Gao, Yu-Xia; Shi, Li-Ying; Liu, Xiao-Qin; Jiang, Yao; Sun, Lin-Bing
Abstract: Au-containing catalysts are highly active in diverse reactions, and their activity strongly depends on the dispersion degree of Au. Here we report for the first time a solid-phase reduction strategy to promote Au dispersion in template-occluded SBA-15 (AS) by fully considering three crucial factors, namely (i) the interaction between Au and supports, (ii) the space where Au precursors locate during reduction, and (iii) the reduction method. First, both template and silica walls in AS offer interaction with Au species. Second, AS presents confined spaces between template and silica walls. Third, the reduction in solid phase avoids the competitive adsorption of solvent molecules. The results show Au-containing AS has a better dispersion of Au than its counterpart prepared from template-free SBA-15 (CS). Moreover, the obtained materials exhibit excellent catalytic activity in reduction reactions and that the organic template retained in mesopores promotes the reactions greatly. Graphical abstract: Highlights: The confined space hinders the aggregation of Au and retains the catalytic activity. The SPR strategy avoids the competitive adsorption of solvent molecules with guests. Highly dispersed Au species are highly active for catalytic reduction reactions. The template favors the dispersion of Au and the enhancement of catalytic activity.